2012
DOI: 10.1186/1471-2318-12-68
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of muscle strength and muscle power training and detraining on physical function in community-dwelling prefrail older adults: a randomized controlled trial

Abstract: BackgroundAlthough resistance exercise interventions have been shown to be beneficial in prefrail or frail older adults it remains unclear whether there are residual effects when the training is followed by a period of detraining. The aim of this study was to establish the sustainability of a muscle power or muscle strength training effect in prefrail older adults following training and detraining.Methods69 prefrail community-dwelling older adults, aged 65–94 years were randomly assigned into three groups: mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
2
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 30 publications
(47 reference statements)
8
116
2
8
Order By: Relevance
“…Groups such as those recovering from hospitalization and immobilization might benefit from nutritional supplementation, even while potentially unable to exercise. Although structured physical activity programs are not always practical or feasible, and maintaining good compliance is often problematic, 52 ideally, this nutrition intervention would be combined with exercise. A recent study demonstrated a reduction in major mobility impairment after a longterm structured physical activity program.…”
Section: Discussionmentioning
confidence: 99%
“…Groups such as those recovering from hospitalization and immobilization might benefit from nutritional supplementation, even while potentially unable to exercise. Although structured physical activity programs are not always practical or feasible, and maintaining good compliance is often problematic, 52 ideally, this nutrition intervention would be combined with exercise. A recent study demonstrated a reduction in major mobility impairment after a longterm structured physical activity program.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that regarding the functional performance of the participants, the muscle strength training group outperformed the muscle power training group. In addition, Zech et al (2012) conducted a randomised controlled trial targeting older adults aged 65-94 years living in communities. A 36-week study was conducted by applying random allocation, and the results showed that muscle power training enabled prefrail older adults to maintain longer periods of physical function.…”
Section: Phases Of Frailty and Mortalitymentioning
confidence: 99%
“…Combinations of resistance and balance training describe in general a consecutive order, where resistance and balance exercises are executed within the same training session or within the same training block. Those exercise interventions have also shown positive effects on measures of strength, power and balance in older adults [911]. …”
Section: Introductionmentioning
confidence: 99%